Happy feet [videorecording (DVD)] - Miller, George, 1945 March 3-; Wood, Elijah, 1981-; Murphy, Brittany; Jackman, Hugh (Warner Home Video, 2007)
Emperor Penguins from Antarctica each express their true love with a special heartsong of their own that expresses their very being. However, the misfit Mumble cannot sing. Instead he has an extraordinary talent to tap dance with almost magical energy and expression. Nevertheless, the leadership of the colony fearfully blames the young penguin's unorthodox ways for the lean fishing that threatens them all. Defiant in the face of unjust rejection, Mumble and his true friends set out to find the true cause of the famine. Through the friends trials and perils, Mumble learns many things about his frozen world, not the least of which being that his toe tapping talent may be what he needs to save his people.